Is there any deixis here?: the analysis of deixis in a textbook of elementary school - Pertiwi, Canda Ayu Arum; Elfiyanto, Sonny (LPPM Universitas Mercu Buana Yogyakarta, 2023)
A language is a device of sounds and written symbols utilized by the humans of a particular country or area to communicate with each other. Pragmatics is a linguistic study that learns the listeners' interpretation. Deixis, which is applied in this research, is one of the pragmatic studies. The researcher used the descriptive qualitative method in this research. The data sourcing of this research is three descriptive texts adopted from a second-semester textbook for elementary school level entitled